Prevalence of undiagnosed uterine leiomyosarcoma in women undergoing hysterectomy or myomectomy for benign indications. (September 2017) - Lange, Sören; Pluchino, Nicola; Fehlmann, Aurore; Marci, Roberto; Boukrid, Meriem; Jazia, Inès Ben; Petignat, Patrick; Dubuisson, Jean
Abstract: Objective: To determine the prevalence of undiagnosed uterine leiomyosarcoma (LMS) in women undergoing hysterectomy or myomectomy for suspected benign leiomyomas. Study design: Retrospective, single-centre, cohort study. Information for all gynaecological procedures for suspected benign leiomyomas between 1993 and 2016 was extracted from the hospital database. The prevalence of LMS was calculated by surgery type and age group. Results: The prevalence of LMS was 1.7/1000 [one in 603 women; 95% confidence interval (CI) 0.8–3.4] for all procedures combined. The prevalence of LMS was 1.1/1000 (one in 875 women; 95% CI 0.4–2.9) for all hysterectomies combined and 4.2/1000 (one in 240 women; 95% CI 1.4–12.2) for all myomectomies combined. For women aged <50 years, the prevalence of LMS was 5.4/1000 (one in 187 women; 95% CI 1.8–15.6) for abdominal hysterectomies, 1.0/1000 (one in 1040 women; 95% CI 0.2–5.4) for laparoscopic hysterectomies, 5.2/1000 (one in 191 women; 95% CI 0.9–29.1) for abdominal myomectomies, 3.0/1000 (one in 332 women; 95% CI 0.5–16.9) for laparoscopic myomectomies and 8.6/1000 (one in 116 women; 95% CI 1.5–47.2) for hysteroscopic myomectomies. Conclusions: Occult LMS is a rare malignant disease. This study found that the prevalence of LMS was higher in women undergoing myomectomy compared with women undergoing hysterectomy. The highest prevalence of LMS was found in women undergoing hysteroscopic myomectomy.